STUDI TENTANG BENTUK DAN MAKNA MOTIF UKIRAN PADA MASJID ASASI DI KOTA PADANG PANJANG - Rofiqel Hayat, Dr. Ramalis Hakin, M.Pd., Drs. Wisdiarman, M.Pd. (Universitas Negeri Padang, 2016)
The purposes of this study were to (1) describe the shape of carving design in Masjid Asasi Kota Padang Panjang, (2) to describe the meaning of carving design in Masjid Asasi Kota Padang Panjang. The type of this research uses qualitative research in which specifically attributed to descriptive. The data of the research comes from the carving design in Masjid Asasi. The source of the research is given by an informan who does comprehend about Minangkabau carving and Masjid Asasi. The data is assembled through observation, interview and documentation. The research finds that there are 15 shapes of the carving design in Masjid Asasi Kota Padang Panjang. Based on the research, it can be concluded that the carving design in Masjid Asasi comes from nature consist of animal, plan, and geometry. The meaning of the carving design in Masjid Asasi is as a model value and prohibition which is engraved in the Masjid’s wall for hundred years.Kata kunci: motif ukiran,bentuk, makna, Masjid.